Development of Radiography of Bed Terminally Ill Patients and Elderly Patients Using an Adjustable Sitting Set - สำราญ กัญรัสมิ์; กุลเพชรจารุกร กาญจณ์ฉัตตร์ (Journal of Health Science of Thailand, 2021)
In Nongkee Hospital, Burirum Province, Thailand, there were 856 patients receiving chest and abdomen radiography services in 2019. The objective of this study was to develop an innovation for performing successful chest and abdomen radiography in order to reduce the delay in assist physicians in providing rapid diagnosis and prompt treatment of the patients. The study samples were patients receiving X-rays services who were unable to sit or stand, particularly those with bedridden, terminally ill or ageing conditions diring the study period from December 2018-November 2019. There were 722 of them (7.1%) from 10,170 cases requiring radiography. Due to the difficulty in handling the patients during taking chest and abdomen radiographs in the situation of limiting equipment or personnel in holding the patients resulting in time-consuming process and low quality radiograph, the authors had devloped a sitting set which could be adjusted the patient position to 45, 60, 90 or 180 degree inclination. The radiation plate was to be placed in the grill at the back of the patient. Upon using the set with the patients, it was found that the set could be easily movable and could be used with an over-weight patient up to 80 - 130 kg. Efficiency of the sitting set was evaluated with 722 patients, and the findings revealed that 100.0% of the radiographs were of high quality standard, and high satisfaction was observed among all physicians, staff, and the patients. The duration of service was within 3 minutes; and there was zero incident of repeated radiography. Finally, there was no incident of fall or faint in all patients while taking the X-ray imaging.